The Influence of Complex Subway Station Construction on High Retaining Walls and Appropriate Countermeasures. (31st July 2020) - Wang, Kai; Li, Zhaoping; Xu, Xuezhao; Shi, Leilei; Zhang, Fanbo
Abstract : Anzhen Bridge Station of Beijing metro line 12, which adopts a separated-island platform constructed by the undermining method, passes along the retaining wall of the North Third Ring Road. A numerical simulation method is adopted to study the deformation laws of the retaining wall under the influence of station construction. The simulation data show that the affected retaining wall will have large settlement and tilt, and countermeasures must be taken. Four countermeasures are formulated, and their control effects are analyzed. The calculation results show that the combination of anchor cables and waist beams can effectively control the tilt of the retaining wall, but the control effect on the absolute settlement is not obvious. The control effect of isolation piles is better than that of foundation grouting. The joint control method of anchor cables combined with waist beams, isolation piles, and deep hole grouting makes the deformation meet the target, and according to this measure, a concept of joint control aiming at the influence of the "source, " "propagation, " and "object" is proposed, which can provide a reference for similar projects with a great difficulty in deformation control.